THE EXISTENCE OF GTM IN TEACHING ENGLISH TO CURRENT STUDENTS - Eros Meilina Sofa (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2019)
This study investigates three problems, which are the practice of Grammar Translation Method (GTM) in English learning for current students, the students’ attitude on learning English using GTM, and characteristics of students which are best taught using this method. In order to get the data, this study used a qualitative approach to analyze the data and it is a kind of case study. The researcher observed the classroom activity and delivered the questionnaire to the students. After getting the result and analyzing the data, this study draws some conclusions. First, GTM is still effective and needed to teach English to current students. Second, not only passive, but also active students who can take benefits from the implementation of this traditional method because it does not perform pure passive learning, but it is also adjusted with the current students’ characteristics. Third, both fast and slow learners are able to follow the lecturer’s instruction when he teaches using GTM because this method accommodates what the slow learners need to achieve the learning goals. Keywords: Grammar Translation Method, Current Students, English Learning